The moderating role of stigma in the relationship between depression and resilience: results of a cross-sectional study in university students - Rometsch, Caroline; Mansueto, Giovanni; Ceccatelli, Sara; Cosci, Fiammetta (Frontiers in Psychology, 2024)
Background/objective Depression is a growing concern in university students and resilience has shown to play a protective role. The impact of stigma is still under-explored, with reference to its moderating role between depression and resilience. The present study investigate such a relationship among Italian university students. Methods A cross-sectional design was applied in a simple of 1,912 students to examine the interrelationships between depression (Patient Health Questionnaire-9), resilience (Nicholson McBride Resilience questionnaire), and stigma (Stigma-9). Correlation, predictor, and moderation analyses were applied in RStudio. Results A negative correlation was found between depressive symptoms and resilience (r = −0.455, p < 0.001). A positive correlation was found between depressive symptoms and stigma (r = 0.207, p < 0.001). Lower levels of resilience and higher levels of stigma were significant predictors of depressive symptoms [F(df, n) = 190.8(3, 1884), p < 0.001, R2 = 0.236]. The moderation analysis showed a weakening of resilience protective effect against depression as stigma levels increase [F(df,n) = 186.7(3,1908), p < 0.001, R2 = 0.226]. Conclusion Stigma influences the relationship between depression and resilience. Anti-stigma interventions and programs empowering resilience, should be implemented in university settings to protect students from depression.